Ritual Poetry and the Politics of Death in Early Japan - Ebersole, Gary L. (Princeton University Press, 2021)
This examination of death rituals in early Japan finds in the practice of double burial a key to understanding the Taika Era (645-710 A.D.). Drawing on narratives and poems from the earliest Japanese texts--the Kojiki, the Nihonshoki, and the Man'yoshu, an anthology of poetry--it argues that double burial was the center of a manipulation of myth and ritual for specific ideological and factional purposes. "This volume has significantly raised the standard of scholarship on early Japanese and Man'yoshu studies."--Joseph Kitagawa "So convincing is the historical and religious thought displayed here, it is impossible to imagine how anyone can ever again read these documents in the old way."--Alan L. Miller, The Journal of Religion "A central resource for historians of early Japan."--David L. Barnhill, History of Religions